2022
DOI: 10.3390/crops2040032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Secondary Metabolites Responsible for the Resistance of Local Tomato Accessions to Whitefly (Bemisia tabaci, Gennadius 1889) Hemiptera in Tanzania

Abstract: Plants have developed mechanisms to cope with stresses in their environments as they grow in diverse settings. Such means include releasing plant defense compounds upon attacks by pests or other stressors. Plants with these characteristics are essential as a plant germplasm source for breeding resistance against herbivores and insect pests. Therefore, this study aimed to screen germplasms for whitefly resistance and characterize the secondary metabolites responsible for this. Thirty local tomato accessions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Alves et al [ 57 , 58 ] suggested that variation in secondary metabolites present in cultivars might be the main reason for differing levels of attractiveness to whitefly. Mrosso et al [ 59 ] found a great variation in diterpenes, tetraterpenes, alkaloids, carotenoids, and fatty acid esters content among tomato cultivars, which influences the level of attractiveness of certain cultivars to whitefly. Similarly, Jaccard et al [ 60 ] reported variations in cucurbitacin levels in different squash cultivars, which impact the feeding behavior of herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Alves et al [ 57 , 58 ] suggested that variation in secondary metabolites present in cultivars might be the main reason for differing levels of attractiveness to whitefly. Mrosso et al [ 59 ] found a great variation in diterpenes, tetraterpenes, alkaloids, carotenoids, and fatty acid esters content among tomato cultivars, which influences the level of attractiveness of certain cultivars to whitefly. Similarly, Jaccard et al [ 60 ] reported variations in cucurbitacin levels in different squash cultivars, which impact the feeding behavior of herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites such as phenolic compounds present in plants confer properties such as antifeedant by repelling phytophagous insects (Talukder et al, 2021). Mrosso et al (2022) indicated that flavonoids are toxic to whiteflies, thus protecting tomato plants from their infestation and damage. Therefore, it can be inferred from this study that the varieties that showed resistance to H. armigera had some secondary metabolites liable for the resistance in Anaya F1, the most resistant variety, has 75.3 mg/100 flavonoids and 183.9 mg/100 phenol.…”
Section: Discussionmentioning
confidence: 99%